غیر مسلموں کے بارے میں مستشرقین اور مرتدین اسلام کے افکار و منہج:ایک علمی و تنقیدی جائزہ: ORIENTALIST AND APOSTATE APPROACHES TOWARDS NON-MUSLIMS: AN ANALYTICAL AND CRITICAL STUDY (Al-Aasar, 2025)
This research critically examines the intellectual and methodological frameworks of both Orientalists and apostates regarding non-Muslims in the context of Islam. It seeks to explore the ideological convergence between these two seemingly distinct groups, especially in their objectives, rhetoric, and conclusions concerning Islamic teachings about non-Muslims. The study delves into how Orientalist discourse, grounded in colonial and post-Enlightenment paradigms, often mirrors the rhetoric of modern apostates who emerge from within Muslim societies. These groups commonly portray Islamic teachings on non-Muslims as inherently intolerant or supremacist, ignoring the comprehensive and nuanced treatment of humanity in Islamic thought.The paper further highlights the responses of prominent Muslim scholars such as Allama Shibli Nu‘mani, Sayyid Qutb, Dr. Hamidullah, and Dr. Fathi Yakan, who provided structured and scholarly refutations based on Qur’anic principles, prophetic traditions, and rational argumentation. Modern Islamic scholarship, aided by academic methodologies and linguistic analysis, continues to challenge Orientalist and apostate assertions with a blend of traditional knowledge and contemporary research tools.In addition, the paper discusses the influence of Orientalist and apostate narratives within Western universities, media, and digital platforms, noting how curricula, media framing, and social networks contribute to shaping perceptions about Islam and its stance on non-Muslims. This research concludes by offering a balanced Islamic perspective based on original sources, emphasizing justice, mercy, and human dignity.